Eggshells: A novel bio-filler for intumescent flame-retardant coatings - Yew, M.C.; Sulong, N.H.R.; Yew, M.K.; Amalina, M.A.; Johan, M.R. (2015)
The aim of this study was to develop intumescent flame-retardant coatings that incorporate chicken eggshell (CES) waste as a novel eco-friendly bio-filler. Three flame-retardant additives, namely, ammonium polyphosphate phase II, pentaerythritol and melamine were mixed with flame-retardant fillers and acrylic binder to synthesize the intumescent coatings. The fire performance of the coatings was evaluated in accordance with 'BS 476: Part 6-Fire Propagation' and 'BS 476: Part 7-Surface Spread of Flame' test standards. It was found that 4 out of 5 of the coated specimens (B, C, D and E) neither showed surface spread of flame nor any afterglow combustion upon fire exposure. The addition of 5.0 wt and 2.5 wt eggshell bio-filler into formulations B and E, respectively, improved fire protection due to char formation, with better morphology, height and structure of the protecting shield. The filler compositions of samples D (3.4 wt TiO2/3.3 wt Al(OH)3/3.3 wt Mg(OH)(2)) and E (2.5 wt TiO2/2.5 wt Al(OH)(3)/2.5 wt Mg(OH)(2)/2.5 wt CES) applied at a thickness of 1.5 +/- 0.2 mm achieved the lowest fire propagation index with a value of 4.5 and 5.0, respectively (BS 476 Part 6, Class 0 materials) which indicates excellent fire-stopping properties. The results showed that the coatings were effective in fire protection, with good qualities of water resistance, thermal stability, and adhesion strength. Significantly, coating E (with CES) has proved to be efficient in the protection of plywood against fire. (C) 2015 Elsevier B.V. All rights reserved.